Improvement of ferroelectric properties in undoped hafnium oxide thin films using thermal atomic layer deposition - Luo, Jun-Dao; Zhang, He-Xin; Wang, Zheng-Ying; Gu, Siang-Sheng; Yeh, Yun-Tien; Chung, Hao-Tung; Chuang, Kai-Chi; Liao, Chan-Yu; Li, Wei-Shuo; Li, Yi-Shao; Li, Kai-Shin; Lee, Min-Hung; et al. (My University, 2019)
Modulating the water pulse time during thermal atomic layer deposition is an effective approach to enhancing the ferroelectric properties of undoped HfO2 thin films. Through grazing incidence X-ray diffraction (GI-XRD), it was observed that a shorter water pulse time can inhibit formation of the monoclinic phase and thereby obtain good remanent polarization. Transmission electron microscopy (TEM) images and GIXRD analysis were used to reveal the crystallization conditions of the undoped HfO2 thin films. By modulating the water pulse time during deposition of all samples, no impurities were found in these films via X-ray photoelectron spectroscopy. Moreover, samples with shorter water pulse times revealed lower binding energy and higher leakage current. However, electric measurement results of samples with shorter water pulse times revealed a higher remanent polarization of approximately 9 mu C cm(-2) and a coercive field of similar to 1.95 MV cm(-1) compared with other samples. After endurance testing, the films lasted for more than 10(8) cycles at 2.25 V, so they are ideally suited to low-power ferroelectric CMOS devices and nonvolatile memory applications. (c) 2019 The Japan Society of Applied Physics